Kajian Teologis Kerajaan yang di Tunda Menurut Injil Matius - Paulus Suyatno; Paulus Kunto Baskoro (STTII PURWOKERTO, 2023)
Jesus came to earth to establish His Kingdom. The Kingdom of Jesus is a Kingdom that cannot be shaken. Jesus hoped that the Jews would receive the Kingdom that Jesus was offering with some Jesus saying, “Repent, for Kingdom of God is near.” This shows that the Kingdom will be established and Jesus conveyed to the Jews the time of His coming to the wolrd. However, in reality, the kingdom that Jesus offered was not well recerived, so that in the Gospel of Matthew, he theological concept appears that the Delayed Kingdom. Through this article, the author will focus on revealing some of the theological concepts referred to about the Delayed Kingdom in the Gospel of Matthew. This research uses descriptive qualititative method. Namely by studying the theological concept of Delayed Kingdom from several book or literature references. The purpose of this study is Frist, to reveal in detail what is meant by Delayed Kingdom. Second, it provides pratical implementation of The Delayed Kingdom concept in today’s modern perspective.